Analisis Perilaku Wajib Pajak Terhadap Kepatuhan Wajib Pajak Dengan Mediasi Niat Menggunakan E-FIlLING Di Kalimantan Timur Tahun 2017 - Purba, Alan Smith; Kaluge, David (Arthavidya Jurnal Ilmiah Ekonomi, 2019)
This study aims to examine the behavior of taxpayers towards taxpayer compliance by mediating the intention to use e-filing in Indonesia, especially in East Kalimantan. The data source in this study is premier data by conducting a survey of individual taxpayer respondents who have used the e-filling facility from 2015 and filled out the questionnaire provided. Before giving the questionnaire this study used the validity and reability test for each question in the questionnaire. The results of this study indicate that the intention to use e-filling has a significant influence on taxpayer compliance in 2017 Key Word: Behavior of Taxpayers,Taxpayer compliance, E-Filling